Defining Plasma MicroRNAs Associated With Cognitive Impairment In HIV‐Infected Patients. Issue 4 (April 2016) - Kadri, Ferdous; LaPlante, Andrea; De Luca, Mariacristina; Doyle, Lisa; Velasco‐Gonzalez, Cruz; Patterson, Jonathan R.; Molina, Patricia E.; Nelson, Steve; Zea, Arnold H.; Parsons, Christopher H.; Peruzzi, Francesca
Abstract : Human Immunodeficiency Virus (HIV)‐infected individuals are at increased risk for developing neurocognitive disorders and depression. These conditions collectively affect more than 50% of people living with HIV/AIDS and adversely impact adherence to HIV therapy. Thus, identification of early markers of neurocognitive impairment could lead to interventions that improve psychosocial functioning and slow or reverse disease progression through improved treatment adherence. Evidence has accumulated for the role and function of microRNAs in normal and pathological conditions. We have optimized a protocol to profile microRNAs in body fluids. Using this methodology, we have profiled plasma microRNA expression for 30 age‐matched, HIV‐infected (HIV + ) patients and identified highly sensitive and specific microRNA signatures distinguishing HIV + patients with cognitive impairment from those without cognitive impairment. These results justify follow‐on studies to determine whether plasma microRNA signatures can be used as a screening or prognostic tool for HIV + patients with neurocognitive impairment. J. Cell. Physiol. 231: 829–836, 2016. © 2015 Wiley Periodicals, Inc.